Gendered institutions and women's political representation in Africa (Africa Now, 2020)
During the course of the past three decades efforts of democratisation and institutional reforms have characterised the African continent, including demands for gender equality and women's political representation. As a result, some countries have introduced affirmative action measures, either in the aftermath of conflicts or as part of broader constitutional reforms, whereas others are falling behind this fast track to women's political representation. Utilising a range of case studies spanning both the success cases and the less successful cases from different regions, this work examines the uneven developments on the continent. By mapping, analysing and comparing women's political representation in different African contexts, this book sheds light on the formal and informal institutions and the interplay between these that are influencing women's political representation and can explain the development on women's political representation across the continent and present perspectives on an 'African feminist institutionalism'.